2021
DOI: 10.1136/neurintsurg-2021-018000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anesthetic strategy on outcomes for patients with acute basilar artery occlusion undergoing mechanical thrombectomy

Abstract: BackgroundThe best anesthetic management strategy for patients with acute large vessel occlusion treated with mechanical thrombectomy (MT) remains uncertain. Most studies have focused on anterior–circulation stroke caused by large artery occlusion. Nevertheless, limited data are available on the appropriate choice of anesthetic for acute basilar artery occlusion (BAO). We aimed to investigate the effect of anesthetic method on clinical outcomes in patients with BAO undergoing MT.MethodsPatients undergoing MT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
2
10
0
1
Order By: Relevance
“…The sensitivity analysis showed that the data from studies focusing on functional independence, 90-day mortality, and successful reperfusion were relatively consistent (Supplemental Digital Content 7, http://links.lww.com/JNA/A560: Figure showing sensitivity analysis). Only 3 studies had minor inconsistencies in favorable outcome, but the estimated OR and border of 95% CI was very close to the combined result (Du et al16 OR: 0.71; 95% CI, 0.51 to 1.08; Li et al18 [GA vs. CS comparison] OR: 0.49; 95% CI, 0.20 to 1.16; Weyland et al21 OR: 0.57; 95% CI, 0.30 to 1.07; pooled results, OR: 0.55; 95% CI, 0.32 to 0.93). The low-quality, high risk bias RCT (Hu et al17) reported only the result of successful reperfusion and not the rate of functional independence, favorable outcome or 90-day mortality.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…The sensitivity analysis showed that the data from studies focusing on functional independence, 90-day mortality, and successful reperfusion were relatively consistent (Supplemental Digital Content 7, http://links.lww.com/JNA/A560: Figure showing sensitivity analysis). Only 3 studies had minor inconsistencies in favorable outcome, but the estimated OR and border of 95% CI was very close to the combined result (Du et al16 OR: 0.71; 95% CI, 0.51 to 1.08; Li et al18 [GA vs. CS comparison] OR: 0.49; 95% CI, 0.20 to 1.16; Weyland et al21 OR: 0.57; 95% CI, 0.30 to 1.07; pooled results, OR: 0.55; 95% CI, 0.32 to 0.93). The low-quality, high risk bias RCT (Hu et al17) reported only the result of successful reperfusion and not the rate of functional independence, favorable outcome or 90-day mortality.…”
Section: Resultssupporting
confidence: 56%
“…These 8 studies included 1777 patients and compared GA with non-GA in patients with acute posterior circulation stroke undergoing EVT (Table 1). Of the included studies, 1 was a case-control study,15 6 were cohort studies, and 1 was an RCT 16–22. There were 3 groups (GA, CS, and LA) in the study by Li et al,18 so we divided them into 2 groups for comparison (GA vs. CS and GA vs. LA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early retrospective studies demonstrated that CS was superior,1 but subsequent randomized controlled trials failed to show the superiority of one method 2–4. Current research continues to explore the best use of anesthesia in acute ischemic stroke therapy 5–8. While consensus does not exist on whether CS or GA is safer and/or more beneficial for stroke interventions, there are strong arguments to support having an anesthesia team involved in all mechanical thrombectomy procedures, whatever method is chosen.…”
mentioning
confidence: 99%